Analysis of Tuned Liquid Damper in Controlling Earthquake Response of Multistorey Building - Rahamat Ali Ansari (AG Volumes, 2021)
Most buildings were constructed in the past with various laws depending on which nation you were in, thus retrofitting is required nowadays. New kinds of structures and uses are emerging, and rules are being revised at the same time. This means that the traditional techniques of constructing earthquake resistant buildings may not be as effective as they once were. This paper aims to provide a comprehensive review on the most common triggering factors of progressive collapse of RC structures such as blast, fire, earthquake, gas explosion, etc. Different zones are studied and compared here.